Vochysia pongo-qonecensis (Vochysiaceae), a new species from the Peruvian Andean-Amazonian piedmont forests - Huamantupa Chuquimaco, Isau (2022)
Vochysia pongo-qonecensis is described and illustrated. It occurs in the southern Peruvian pre-montane forests of the Andean-Amazonian piedmont. This species is placed in Vochysia sect. Ciliantha subsect. Micranthae. It has some morphological similarities with V. citrifolia and V. parviflora.